RITUAL AESTHETICS OF ACI SANG HYANG GRODOG CEREMONY IN LEMBONGAN KLUNGKUNG VILLAGE, BALI - Pramada, I Gede Yuda; Mariasa, I Nengah (Sembadra, Journal of Arts and Education Studies, 2021)
This study aims to determine the aesthetic meaning of the Sanghyang Grodog ritual in Lembongan Village, Klungkung Bali, which has its own and unique characteristics, different from other Sanghyang in Bali. The uniqueness and number of dances in Sanghyang Grodog ceremony attracts further investigation to capture the meanings that exist in the Sanghyang Grodog. Aci Sanghyang Grodog is a ritual art that is believed by the local community as a medium of ceremony to prevent the emergence of calamities that disturb the villagers, including drought and epidemics of deadly diseases as well as the ceremony to ask to the greatness of God to maintain harmony and balance in the universe. As a ritual or ceremony, Sanghyang Grodog has a special concept of presentation starting from actors, stages of performance, performance structure and so on. This research will examine the problem of the aesthetic meaning of the Sanghyang Grodog ritual. Sanghyang Grodog is a "ceremony to ask for salvation" which is performed every two years. This is done to neutralize negative elements so that they become positive. The elements that have been neutralized by the Sanghyang Grodog ritual are believed to have a good overall impact on the environment and community of Lembongan Village and the universe as a whole. This research was conducted using qualitative research methods where all data were obtained from participant observation, interviews, literature study and documentation. Data analysis was performed by reducing, clarifying, describing, concluding and interpreting all information selectively. Keywords: Aesthetics, Ritual, Sanghyang Grodog